Survey of anger, psychological well-being, resilience and social capitals of adolescents and youth, adults and middle- aged 15 to 60 (Comparative study) - Saraee, Soheila; Shabani, Somayeh; Reshetnikov, Mikhail (Advances in Social Sciences Research Journal, 2020)
Background:Studies show that there are many factors that contribute to anger, and many psychological components can lead to increased anger management mechanisms. There are also differences in the amount of this component based on demographic indicators in different age groups. Therefore, considering the importance of this issue in this study, the differences between these components in different age groups and based on demographic indicators were investigated. Purpose:Given the importance of demographic indicators in the occurrence of anger indicators, psychological well-being, resilience and social capital in this study, the purpose of this study was to compare the anger, psychological well-being, resilience and social capital in adolescents and youth, adults and middle-aged 15-60 years, as well as compare these variables based on gender, marital status and levels of education. Method:This study is a causal-comparative study and multivariate analysis of variance (Manova) with respect to the assumptions will be used to analyze the data. The statistical population included adolescents and youth aged 15 to 20, adults 21 to 40, and middle-aged 41 to 60 years. In this study, 400 individuals were selected by random sampling. The ages of participants ranged from 15 to 60 years. There were equivalent numbers of men (n=84) and women (n=189). More participants (n=109) were unmarried than were married (n=94), %39.9 (unmarried), %34.4 (married) and %25.7 It has been unanswered. Also, 34.4% of the participants were adolescents and youth people, 34.4% were adults people and 31.1% were middle-aged people. Also, 20.9% of the sample had undergraduate education, 22% had a diploma degree, 24.9% had a bachelor's degree, 12.1% had a master's degree or higher, and 20.2% had no answer. Findings:the results showed that the difference between the three age groups in the psychological well-being component is confirmed. based on the adjusted averages, it can be said that with 95% confidence, the middle-aged group had the highest average in the psychological well-being component. It was also revealed that there is no difference between any of the variables of Anger variables, psychological well-being, resilience, and social capital in the two groups of men and women. Also, there was a difference between single and married groups is confirmed in the components of Anger variables, Trait anger, State Anger, and psychological well-being. Also, based on the adjusted averages, it can be said that with 95% confidence, the single group had a higher average in anger components than the married group and had lower psychological well-being. Also, the results show that the difference between different educations in the anger component is confirmed. based on the adjusted averages, it can be said that with 95% confidence, the diploma and sub-diploma education groups have a higher average in the component of anger than the masters and doctoral degrees. Conclusion:Aggression and aggressive behavior in children are seen in both boys and girls, although in girls the aggression is less physical than in boys and is associated with less physical harm. Also, married people seem to experience less negative emotions due to the experience of intimacy, and therefore experience a lower level of anger and higher psychological well-being. People with higher education also seem to have better skills in regulating nothingness and controlling anger due to more training.